Rural-urban and sex-specific disparities in the prevalence of modifiable and metabolic risk factors associated with NCDs including cancer in Northeast India - Anita Nath; Vaitheeswaran Kulothungan; Thilagavathi Ramamoorthy; Vinay Urs K S; Debabrata Barmon; Jaganath Sharma; Anita Bhutia; Tseten Bhutia; Madhubala Devi; Sushma Khuraijam; Kaling Jerang; Ravi Kannan; et al. (Clinical Epidemiology and Global Health)
Problem considered: Cancer is the second leading cause of death globally and in India, following cardiovascular diseases, with most cases linked to modifiable risk factors. This study aimed to determine the prevalence of cancer-related modifiable and metabolic risk factors and assess disparities by rural-urban status and gender in Northeast India. Methods: A population-based cross sectional study was conducted from 2019 to 2021 in 12 Population-Based Cancer Registries across eight northeastern states, involving 23,040 adults aged >18. Data on socio-demographics, lifestyle, anthropometric, and biochemical parameters were analysed using weighted sampling and SPSS software. Results were reported as means and proportions with 95 % confidence intervals. Results: A total of 21321 respondents completed the survey, indicating a response rate of 92.5 %. Tobacco use was reported by 48.6 %, significantly higher in rural men (64.2 %) than in urban men (58.3 %) (p < 0.001). Smokeless tobacco use was significantly more in women (30.7 %) than men (22.9 %) (p < 0.001). Ever consumption of alcohol consumption was significantly higher among men (47.2 %) and rural residents (33.1 %) (p < 0.001). Women (91.7 %) and rural residents (93.3 %) were more physically active than men (88.2 %) and urban residents (85.7 %) (p < 0.001). Hypertension (stages 1 and 2) affected more men (29.1 %) and urban residents (28.9 %) (p < 0.001). Overweight affected 22.4 %, obesity 5.2 %, with significantly higher obesity rates in women (6.3 %) and urban residents (7 %) (p < 0.001). Clustering of more than three risk factors was observed in 31.3 % of participants, significantly higher among men (37.1 %) and urban participants (37.3 %) (p < 0.001). Conclusion: The higher prevalence of risk factors compared to national estimates may contribute to elevated cancer incidence rates in Northeast India. Understanding these burdens highlights opportunities for cancer prevention and control. Findings underscore the importance of sustained cancer risk factor surveillance in cancer registry areas.